FRI0323 Level of physical activity in primary sjögren's syndrome and its predictors. (23rd January 2014) - Ng, W.-F.; Miller, A.; Bowman, S.; Price, E.; Kitas, G.; Pease, C.; Emery, P.; Lanyon, P.; Hunter, J.; Gupta, M.; Giles, I.; Isenberg, D.; et al.
Abstract : Background: There is now clear evidence that supports the health promoting and disease preventing benefits of physical activity. To date, little research has been undertaken to evaluate physical activity levels in primary Sjögren's syndrome (PSS) patients. Many symptoms of PSS such as musculoskeletal pain and fatigue may affect the ability and desire to participate in physical activity. Objectives: To evaluate the levels of physical activity in individuals with PSS and its relationship to other clinical features of PSS. Methods: Self-reported levels of physical activity from 273 PSS patients were collected using International Physical Activity Questionnaire (IPAQ) short form. The data were compared with healthy controls matched for age, sex and body mass index. Fatigue and other clinical aspects of PSS including disease status, dryness, daytime sleepiness, dysautonomia, anxiety and depression were assessed using validated tools. Univariate correlation and stepwise regression analyses were used to explore the relationships between physical activity levels and clinical features of PSS Results: Individuals with PSS had significantly reduced levels of physical activity (median (interquartile range, IQR) MET*min/week: 1572 (2564) versus 3708 (6523), p<0.001), but similar levels of sedentary activity (median (IQR) min: 300 (188) versus 343 (214), p=0.532) compared to healthy individuals. The differences in physical activity were more profound at moderate (median (IQR) MET*min/week: 0 (480) versus 1560 (3330), p<0.001) and vigorous intensities (median (IQR) MET*min/week: 0 (480) versus 480 (1920), p<0.001). Univariate correlation analysis revealed significant association between physical activity and gender, fatigue, orthostatic and depressive symptoms. Sedentary activity did not correlate with fatigue. Stepwise regression analysis identified gender, physical fatigue and dryness as independent predictors of levels of physical activity. Conclusions: Physical activity is reduced in people with PSS, particularly in moderate to vigorous intensity levels. Gender, fatigue and dryness are independently associated levels of physical activity. Acknowledgements: This work was supported by the Medical Research Council (G0800629) and the British Sjögren's Syndrome Association. This project also received infra-structure support from the Northumberland, Tyne and Wear Musculoskeletal Comprehensive Local Research Network and the Newcastle Clinical Research Facilities. Disclosure of Interest : None Declared